Emotional Competence, Family Social Support and Parental Stress in Mothers of Children with Autism during the Pandemic - Dinie Ratri Desiningrum (Journal of Educational, Health and Community Psychology, 2022)
This study was aimed to determine the relationship between emotional competence, family social support and parental stress in mothers of children with autism spectrum disorder (ASD). This research was a quantitative research with correlational method. Purposive sampling technique by distributing questionnaires using Google form resulted in a total of 165 participants who are mothers of children with ASD, as members of therapy centers and schools for children with special needs in Semarang, Solo and Yogyakarta. The data were analyzed using structural equation model (SEM) technique on Lisrel program. This research resulted in two models showing that there are fit model with empirical data. The first model shows that each of emotional competence and family social support had a significant effect on parental stress in mothers of children with ASD. The second model shows the influence of emotional competence on the stress of parenting of children with ASD, with family social support as a moderating variable. The implications of this study are empirical evidence on the importance of family social support and emotional competence for mothers in raising children with ASD to prevent excessive parental stress.